Promoting the Enhancement students’ academic achievement through Teacher-student Conferences. Faculty of Education, Souphanouvong University - Souliya, Toulakone (Souphanouvong University Journal Multidisciplinary Research and Development, 2016)
The objectives of this study were to promote the enhancement of students’ academic achievement or GPA. And to demonstrate the teacher-student conference task can improve students in learning or not. The sample group of this study were 20 poor students from 4 classes who are studying in English major, faculty of Education, Souphanouvong University, this conference refers to one-to-one interaction between teacher and student, teacher asked students about his/her problems then the teacher find the way to solve and encourage them. The conference took place twice per week (5 hours/ week, 12 weeks of experiment) at the first semester. Finally, the GPA of pre-semester and post-semester of 20 students were compared in order to see the improvement of students’ academic achievement. The finding revealed that teacher-student conferences could enhance students’ learning achievement. The mean of GPA of pre-semester was 2.1135 with Std = 0.40826 whereas the mean of GPA of post-semester was 2.4720 with Std = 0.39008.while the sig was 0.000.